Sorption extraction of strontium radionuclides from surface water by natural aluminum silicate - Andrey S. Kutergin; Tatiana A. Nedobukh; Aleksandr F. Nikiforov; Ksenia I. Zenkova; Taisiya V. Tarasovskikh (Водное хозяйство России: проблемы, технологии, управление)
The contamination of large volumes of surface waters with radionuclides is caused by the appearance of a significant number of objects that pose a potential radiation hazard. The search and development of affordable, environmentally friendly sorbents for the purification of such waters is an urgent task, the solution of which will make it possible to propose effective measures for the purification of natural water bodies from pollution. The article presents the result of research of sorption reduction of 90Sr radionuclide from aqueous solutions with experimental samples under static and dynamic conditions.